Six days in July: Charles Lyell in the Eifel in 1831 (possibly looking at loess) - Smalley, Ian (Geologos, 2017)
Charles Lyell made a geological excursion to the Eifel region in Germany in July 1831. He went to examine volcanic rocks and volcanic landscapes. He discussed this outing with Mary Somerville and Samuel & Charlotte Hibbert. It is possible that he observed loess in the Eifel. It is hoped that his Eifel notebook is with the Lyell papers at Kinnordy and that it may be transcribed and published. Lyell spread the word on loess; Von Leonard invented it and Horner enthused about it but Lyell disseminated the essential idea of loess. There is (so far) no clear evidence that Lyell saw and appreciated loess in the Eifel region in 1831. This suggests that his first real encounter with the loess (ground or concept) was in the discussions with the Hibberts in September 1831. He certainly had substantial (reported) encounters in 1832, and was definitely interested by the time of the publication of the Principles of Geology vol. 3 in 1833.